Development of a health support competence scale for supervisors of female migrant workers in Japan - Aya Shinohara; Noriko Kuwano; Yoshimitsu Shinagawa; Ryoko Kawasaki; Mayumi Ohnishi (BMC Public Health)
Abstract Background Supervisors of female migrant workers are expected to support their health, as migrant workers play a vital role in Japan’s economic development. However, this support relies on supervisors’ experience and efforts. Enhancing their competence can improve the quality of support. Therefore, this study aims to develop and validate the Health Support Competence Scale for Supervisors of Female migrant workers (HSCSS-F) to assess their competence in providing health support. Methods The cross-sectional study was conducted in two steps (i.e., preliminary and main studies) using a self-administered questionnaire. In total, 3,401 eligible supervisors were approached across Japan. Construct validity was evaluated using exploratory and confirmatory factor analyses, and reliability was assessed using Cronbach’s alpha for internal consistency. For concurrent validity, the correlation between the HSCSS-F and the Intercultural Sensitivity Scale (ISS) or the Health-oriented Leadership Staff-Care Value (HoL Staff-Care Value) was determined. Results The study extracted 22 items, which categorized into three factors, namely, health support through human resource development or cultural respect, and support for disease prevention and health promotion. Confirmatory factor analysis suggested a model that fit the data well, with a goodness of fit index = 0.903, adjusted goodness of fit index = 0.881, comparative fit index of 0.909, and root mean square error of approximation = 0.068. A Cronbach’s alpha of 0.925 confirmed internal consistency. The total HSCSS-F score was significantly positively correlated with score for ISS (r = 0.502, p < 0.001) or the HoL Staff-Care Value (r = 0.463, p < 0.001). Conclusion The HSCSS-F is a reliable and valid scale. It could provide supervisors not only with an appropriate assessment of support for the health of female migrant workers but also with a course of action. The acquisition and development of competence in the health support by supervisors would contribute to a healthy life for female migrant workers in a host country.